Uporaba računalnika med vzgojitelji in učitelji prvega triletja pri obravnavi družboslovnih vsebin - Plazar, Sonja (Revija za elementarno izobraževanje, 2010)
The use of computers for social studies classes among pre-school teachers and teachers of the first three-years of primary school. This article presents the results of surveys conducted on a sample of pre-school teachers and primary teachers from different statistical regions of Slovenia. The purpose of the study was to determine the frequency of computer use among pre-school teachers and teachers in the 1st three-year cycle. Furthermore, we were also interested in determining whether there are differences between pre-school teachers and primary teachers. We found that in general, computer use in the treatment of social content shows a positive trend. Such a finding is certainly suggestive. We also found that pre-school teachers and primary school teachers prefer to use computers outside of class. Further investigation of the differences between pre-school teachers and primary school teachers show that these results are not encouraging any more. Research has clearly shown that the pre-school teachers in comparison with primary school teachers use computers in their work much less. We must consider the various factors that may affect such an outcome (inadequate equipment, lack of time, lack of training, the developmental rate of pupils, etc.). Because we did not check their compliance in our survey, we can only have a basic understanding of such findings.